2000
DOI: 10.1046/j.1432-1327.2000.01656.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of Edg‐1 receptors in rat cardiomyocytes

Abstract: Recent evidence indicates that sphingolipids are produced by the heart during hypoxic stress and by blood platelets during thrombus formation. It is therefore possible that sphingolipids may influence heart cell function by interacting with G-protein-coupled receptors of the Edg family. In the present study, it was found that sphingosine 1-phosphate (Sph1P), the prototypical ligand for Edg receptors, produced calcium overload in rat cardiomyocytes. The cDNA for Edg-1 was cloned from rat cardiomyocytes and, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 25 publications
1
35
3
Order By: Relevance
“…S1P 1 expression levels were almost twofold greater than those of S1P 3 . Other investigators have also reported high levels of S1P 1 in mouse heart (55) and isolated human (20,36) and rat ventricular myocytes (33,39). S1P 3 has also been routinely identified in myocardium of various species (14,33).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…S1P 1 expression levels were almost twofold greater than those of S1P 3 . Other investigators have also reported high levels of S1P 1 in mouse heart (55) and isolated human (20,36) and rat ventricular myocytes (33,39). S1P 3 has also been routinely identified in myocardium of various species (14,33).…”
Section: Discussionmentioning
confidence: 89%
“…S1P 1 has been detected in abundance in neonatal rat cardiomyocytes (39). In these cells, exposure to S1P (500 nM) results in an initial negative inotropic effect (reduction of systolic calcium).…”
mentioning
confidence: 99%
“…Low ceramide concentration treatment of mitochondria isolated from ischemia-exposed SH-SY5Y neuroblastoma cells resulted in reactive oxygen species (ROS)-induced controlled opening of the mPTP that could reduce mitochondrial Ca 2+ overload and explain the sphingolipid protective mechanism. S1P-mediated Ca 2+ overload in rat cardiomyocytes could be reduced by EDG-1 protein expression inhibition with EDG-1 antisense cDNA transfection [69]. S1P is implicated in the maintenance of increased peripheral resistance in heart failure via p38 MAPK-mediated deactivation of myosin light chain phosphatase [70].…”
Section: Hypoxic Conditions and Cytoprotectionmentioning
confidence: 99%
“…Cellular receptors are a pathway for beneficial or harmful effects of these mediators and a response may depend on receptor subtypes and the signaling pathways it activates in a defined cell [131]. S1P might produce Ca 2+ overload in cardiomyocytes [69]. Blocking of S1P(1)R expression with an antisense approach caused a decrease in S1P-mediated Ca 2+ deregulation, leading to speculation that S1P release by platelets during aggregation and thrombosis, may be involved in acute myocardial ischemia due to S1P's negative inotropic and cardiotoxic effects [69].…”
Section: S1p Status Disturbance Effectsmentioning
confidence: 99%
See 1 more Smart Citation